STRATEGIES FOR IMPROVING CHILDREN'S TOURISM IN THE PRESCHOOL EDUCATION SYSTEM - Haydarova Shakhlo Narzullayevna (American Journals Publishing, 2024)
This article discusses tourism organized in pre-school educational organizations and its impact on the continuous improvement of children's health. The essence of the concept of tourism is revealed. Areas such as organizing tourist trips for preschool children seeing historical and cultural landmarks, learning about their past, discovering cutting-edge construction, opulent homes, exquisite gardens, and acknowledging national customs discovering historical and cultural landmarks, learning about contemporary construction, opulent homes, exquisite gardens, and the acknowledged customs of various cultures.
Keywords: Tourism, walk, travel, excursion, tourism, social-emotional, folk, market economy, educational, necessary component, health, scientific research, socio-economic, mass-cultural events, historical-cultural monuments, rock climbing, ridge mountain, artificial lake, strategy, design.